Modeling and simulation of the non-stationary fading channels under fast time-variant environment - Boyu HUA; Qiuming ZHU; Xiaoxiang HE; Kai MAO (Dianxin kexue)
For solving the problem of non-stationary features in rapid time-varying scenarios,such as high-speed railway,unmanned aerial vehicle and V2X communication,an improved simulation method for non-stationary fading channels was proposed.Introducing the integral items and random offset,this method can revive non-stationary channels under time-variant scattering scenarios and ensure a smooth transition between two adjacent channel states.Numerical simulations show that simulated statistical properties,such as,the probability density function,auto-correlation function,and Doppler power spectral density have good agreements with the theoretical ones.Thus,this method can be applied for wireless channel modeling and communication system evaluation of future high-speed mobile scenarios.